Livelihood Pattern of Suicide Farmers of Vidarbha Region - N.M. Kale; S.R. Khonde; U.G. Thakare (Journal of Agricultural Extension Management, 2025)
In recent years, a larger agrarian crisis, particularly in low rainfall and low irrigation tracts of Vidarbha region of Maharashtra has precipitated a spate of suicide deaths among farmers. This is a matter of serious concern and has been drawing wide attention among the policy makers. As per Government records a total of 2616 farmers committed suicide during 2001 to 2006 in six districts of Vidarbha region viz; Yavatmal, Buldana, Amravati, Akola, Washim from Amravati revenue division and Wardha from Nagpur revenue division